DIGITAL SMART BUSINESS: PENGUATAN PEMASARAN DAN KEUANGAN UMKM TRUTTY’S TAHOE SUTRA DI ERA EKONOMI KREATIF - Albertus Lalaun; Ennis Sarenah Kriekhoff; Theofilus Josias F. K. Matrutty; Melda Dahoklory (BORJUIS: JURNAL OF ECONOMY, 2025)
This Community Service (PkM) program aims to enhance the capacity and competitiveness of Trutty’s Tahoe Sutra MSME through the implementation of the Digital Smart Business concept, which focuses on two key aspects: strengthening digital marketing (e-commerce) and improving simple financial management. The main problems identified were the use of conventional product promotion methods and unstructured financial records, which affected business efficiency and decision-making. The program was carried out through mentoring, training, and hands-on implementation, including the creation of e-commerce accounts, optimization of social media for business promotion, and the application of digital-based financial recording tools. The evaluation was conducted using observation, interviews, and comparative analysis of partner skills before and after the program. The results show a significant improvement in the partner’s ability to utilize e-commerce. Business platforms for online promotion and sales. Moreover, the partner began to implement daily cash records and monthly financial reports independently. This activity demonstrates that integrating digital marketing with simple financial management creates an efficient, accountable, and competitive Digital Smart Business model suitable for micro, small, and medium enterprises in the creative economy era.